2018
DOI: 10.3389/fimmu.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Approaches Towards Cancer and Inflammation: A Cross Talk

Abstract: The inflammation is the protective response of the body against various harmful stimuli; however, the aberrant and inappropriate activation tends to become harmful. The acute inflammatory response tends to resolved once the offending agent is subside but this acute response becomes chronic in nature when the body is unable to successfully neutralized the noxious stimuli. This chronic inflammatory microenvironment is associated with the release of various pro-inflammatory and oncogenic mediators such as nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
195
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 249 publications
(209 citation statements)
references
References 161 publications
(245 reference statements)
6
195
1
7
Order By: Relevance
“…Chronic inflammation takes place for two main reasons: ( i ) the host is unable to eliminate the original stimulus or ( ii ) the host cannot carry out the resolution of inflammation program . Chronic inflammation involves progressive changes in several kinds of inflammatory cells and can participate in the causation of chronic diseases, such as cardiovascular, arthritis, diabetes, neurological diseases and cancer …”
Section: Inflammation and CCmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation takes place for two main reasons: ( i ) the host is unable to eliminate the original stimulus or ( ii ) the host cannot carry out the resolution of inflammation program . Chronic inflammation involves progressive changes in several kinds of inflammatory cells and can participate in the causation of chronic diseases, such as cardiovascular, arthritis, diabetes, neurological diseases and cancer …”
Section: Inflammation and CCmentioning
confidence: 99%
“…32 Chronic inflammation involves progressive changes in several kinds of inflammatory cells and can participate in the causation of chronic diseases, such as cardiovascular, arthritis, diabetes, neurological diseases and cancer. 33 Researchers have suggested that there is a relationship between inflammation and cancer, but this suggestion is not a thoroughly novel idea, because Rudolf Virchow (1863) demonstrated that inflammation and chronic irritation could lead to cancers. 34 Nowadays, inflammation is accepted as a significant cancer hallmark ( Fig.…”
Section: Inflammation and CCmentioning
confidence: 99%
“…Cytokines (interleukins [ILs], growth factors, interferons, etc) play an important role in regulating the inflammatory response, and chronic inflammation and are involved in cancer development . Chronic inflammation is associated with the release of various mediators (pro‐inflammatory and oncogenic ones), such as reactive nitrogen oxygen species, inflammatory cytokines (IL‐1β, IL‐2, IL‐6, and tumor necrosis factor alpha [TNF‐α]), growth factors, and chemokines …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cytokines (interleukins [ILs], growth factors, interferons, etc) play an important role in regulating the inflammatory response, and chronic inflammation and are involved in cancer development. 3,4 Chronic inflammation is associated with the release of various mediators (pro-inflammatory and oncogenic ones), such as reactive nitrogen oxygen species, inflammatory cytokines (IL-1β, IL-2, IL-6, and tumor necrosis factor alpha [TNF-α]), growth factors, and chemokines. 4 Based on their inflammatory activity, cytokines are divided into pro-inflammatory (IL-6, IL-17, IL-18, TNF-α, interferon gamma [IFN-γ], etc) 5 and anti-inflammatory (Il-4, IL-10, IL-13, etc) ones, whereas several cytokines have a dual role (IL-10, IL-22, TGF-β1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation